A Bridge Across Ethnic Lines? Italian Cafes in Welsh Popular Culture and Public History. (1st December 2013) - Giudici, Marco
During the first half of the twentieth century, Italian migrants set up hundreds of cafes throughout the south Wales coalfield. Despite having become a common theme in Welsh popular culture and collective memory, these cafes have been neglected in academic inquiry. This article aims to fill this gap and investigates how Italian cafes have been portrayed and remembered in Welsh popular culture and public history. It argues that the media and other cultural industries have, over the years, flagged cafes as banners of an imagined south Wales community, inspired by principles of proletarian solidarity and cosmopolitanism. This archetypal image of the past has, increasingly over the last thirty years, been built upon by the media in response to growing political, social and economic concerns, which followed the dramatic deindustrialization of the south Wales coalfield. This article shows how, although it corresponds to some extent to historical reality, this way of portraying cafes presents some inevitable problems that undermine rather than enhance the traditional image of a cohesive and supportive south Wales coalmining community.